ADM guidance-ceramics: Fatigue principles and testing. Issue 11 (November 2017) - Kelly, J.R.; Cesar, P.F.; Scherrer, S.S.; Della Bona, A.; van Noort, R.; Tholey, M.; Vichi, A.; Lohbauer, U.
Abstract: Background: Clinical failure of dental ceramics is usually reported as partial fracture of the restoration (chipping) or as catastrophic fracture of the whole structure. In contrast to metals, ceramics are linear-elastic, brittle materials exhibiting extremely low damage tolerance to failure. Well documented clinical and lab reports have shown this fracture event often occurs at loads far below their fracture strength due to intrinsic fatigue degradation via slow crack growth or cyclic fatigue mechanisms. The presence and development of surface flaws have a dominant role in damage accumulation and lifetime reduction of ceramic structures. Aims: This ADM guidance document aims to summarize the aspects related to fatigue degradation of dental ceramics, reviewing the concepts of fatigue testing and furthermore aims to provide practical guidance to young scientists entering into fatigue related research. The description of fatigue strength is always accompanied by a clear understanding of the underlying fracture mechanisms.